The Concept of Justice in Islam: A Literature Review of Tafsir Al-Qur'an and Hadith - Rosidi Sopianto (Journal of Islamic Religious Studies, 2025)
Justice is a fundamental principle in Islam that encompasses various aspects of life, including social, economic, and legal matters. This study aims to analyze the concept of justice in Islam based on the Qur'anic exegesis (tafsir) and Hadith using a literature review method. The primary data sources consist of the Qur'an, Hadith, as well as classical and contemporary tafsir literature. The findings of the study reveal that justice in Islam is not only related to equality but also the granting of rights in accordance with Islamic law (sharia). The Qur'an mentions the concept of justice using the terms al-'adl and al-qist, which refer to balance, equality, and the protection of individual rights. The Hadith of Prophet Muhammad SAW emphasizes the importance of justice in leadership, economic transactions, and social relationships. A study of classical tafsir sources such as Ibn Kathir and Al-Tabari shows that justice in Islam has a strong foundation in sharia law, while contemporary tafsir sources like Muhammad Abduh and Al-Jabiri emphasize its application in social and economic contexts. The findings of this study demonstrate that the concept of justice in Islam is dynamic and can serve as a foundation for the development of an inclusive legal system, fair economic distribution, and harmonious social interactions. Therefore, a deep understanding of justice in Islam through the Qur'anic exegesis and Hadith can contribute to creating a more just and prosperous society.